Creeping Indigo, A Poisonous Plant of Concern in Florida Pastures - Robert MacKay; Ed Jennings; Brent Sellers; Jason Ferrell; Amanda House (EDIS)
A recent rise in suspected horse poisonings has brought new attention to creeping indigo (Indigofera spicata), a toxic plant which has reportedly been in Florida for as long as 90 years. This new 5-page fact sheet covers plant description, signs of creeping indigo toxicity, and roles of creeping indigo’s toxins, as well as treatment and management. Written by Robert MacKay, Ed Jennings, Brent Sellers, Jason Ferrell, and Amanda House, and published by the UF Department of Agronomy, August 2015.